URGENSI KOMUNIKASI DALAM KELOMPOK - Mujahidah Mujahidah (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
As social beings, people always need another people to meet their needs. Therefore, an interaction with other individuals occures in the community. The community can be said as gathering of individuals who do mutual interaction and influence between those to each other. Through the group, people can meet all their needs. In order that group members can exchange information, a tool is needed to connect them, that is, communication through which people can interact, get to khow each other, express what is in their midns to others, as well as they can reach an understanding so that all needs can be met.